The role of affective temperaments in predicting depression and anxiety symptoms in patients with primary hyperparathyroidism - Deniz Alçı; Mustafa Eroğlu; Mehmet Aşık (PLoS ONE, 2025)
Background This study aimed to investigate the relationship between affective temperament traits and the severity of depression and anxiety symptoms in patients diagnosed with primary hyperparathyroidism. Methods A cross-sectional study was conducted including 47 patients with primary hyperparathyroidism and 36 healthy controls. Participants were evaluated using the Memphis, Pisa, Paris and San Diego Temperament Assessment Scale to assess affective temperament profiles, and the Hospital Anxiety and Depression Scale to determine symptoms of anxiety and depression. Clinical, biochemical, and sociodemographic data were also collected. Correlation analyses and a generalized linear model were used to explore associations and predictors of psychiatric symptoms. Data were collected at Çanakkale Onsekiz Mart University between June 2016 and January 2017. Results Patients with primary hyperparathyroidism showed significantly higher scores for depressive, cyclothymic, and anxious temperaments compared to healthy controls. Anxiety and depression scores were also significantly higher in the patient group. Among patients, depressive, cyclothymic, irritable, and anxious temperament traits were positively correlated with both anxiety and depression levels, whereas hyperthymic temperament showed no significant association. Multivariate analysis revealed that anxious and cyclothymic temperaments were significant predictors of anxiety symptoms, while hyperthymic temperament was associated with lower depression scores. No significant associations were found between biochemical parameters and psychiatric symptom severity, except for a positive correlation between serum calcium levels and hyperthymic temperament. Conclusions Affective temperament characteristics, particularly anxious and cyclothymic traits, are closely associated with the severity of anxiety and depression symptoms in patients with primary hyperparathyroidism. Hyperthymic temperament may act as a protective factor against depression in this population. Incorporating temperament assessment into the clinical evaluation of these patients may facilitate early identification of those at higher risk for psychiatric comorbidities and guide more effective, individualized intervention strategies.